Identification processes in the work of the actor - Torres-Vilar, Natalia (2004)
The paper addresses the processes of identification between the actor and the characters he creates. Starting from a chronological review of the concept of identification in the psychoanalytic literature, and intending to differentiate the concept from others than are related, we move towards a review of the scarce existing works on identification applied directly to the acting phenomenon. Since the objective of this research is to observe how the processes of identification effectively take place in the practice of the actor while creating his characters, we interview five respected actors to know their opinions and experience on the subject. The results are based on the experiences shared by the participants.